Evaluation of bonding performance of amino polymers using ABES - N. A. Costa (2014)
In this paper, the use of Automated Bonding Evaluation System (ABES) for evaluation of bonding strength of wood adhesives is presented. A simple reactive model is proposed, which considers the phenomena involved during resin cure: formation of wood-resin-wood bonds. In the present study, experimental data of a standard urea-formaldehyde (UF) resin using different catalysts, phosphoric acid and ammonium sulphate, are presented and discussed. The proposed can be applied to wood adhesives, namely formaldehyde-based resins under different temperatures. The model fits well to experimental data, presenting high determination coefficient values.